Peran Kepala Sekolah Sebagai Pemimpin Pembelajaran Ditinjau dari Permendiknas Nomor 28 Tahun 2010 di SMP IT An-Nisa Dompu - Mujiono Sang Putra; Sofyan Syamratulangi; Kamaluddin (Yayasan Pembina Lembaga Pendidikan (YPLP) PGRI Kabupaten Sumbawa Barat - NTB - Indonesia, 2022)
This study aims to determine the extent of the principal's role as a learning role at SMP IT An-Nisa Dompu, and to determine the extent of the implementation of Permendiknas No. 28 of 2010 concerning the role of school principals and their position in organizing educational units in schools. The type of research used is a qualitative research method, which is carried out by collecting data in the form of numbers, the data in the form of numbers are then processed and analyzed to obtain scientific information behind these numbers. As a school principal, he must have a leadership spirit and be able to provide guidance and supervision, increase the willingness of educational staff, open two-way communication, and delegate tasks. conducive school organization that fosters the spirit of educators and students. With the leadership of the principal, the principal is expected to be able to provide encouragement and contribute to progress that can inspire the process of achieving its goals. Managerial ability is closely related to how the implementation of management functions or management processes, namely planning, organizing, implementing, controlling, and evaluating related to the role of learning leaders